2021
DOI: 10.1186/s40337-021-00396-7
|View full text |Cite
|
Sign up to set email alerts
|

Review: questionnaires as measures for low energy availability (LEA) and relative energy deficiency in sport (RED-S) in athletes

Abstract: Background A sustained mismatch between energy intake and exercise energy expenditure (EEE) can lead to Low Energy Availability (LEA), health and performance impairments characteristic of Relative Energy Deficiency in Sport (RED-S). Questionnaires can conveniently identify symptoms and/or LEA/ RED-S risk factors. This study aimed to systematically identify, and critique questionnaires used or developed to measure LEA/ RED-S risk in athletic populations. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 65 publications
(105 reference statements)
1
45
0
Order By: Relevance
“…The EDE-Q 6.0 was used to measure behavioral and cognitive symptoms of eating disorders the past 28 days (Fairburn and Beglin, 1994 ). The EDE-Q is based on the Eating Disorder Examination Interview which is considered as the gold standard in eating disorder assessment (Guest, 2000 ) and is one of the most used instruments to screen for eating disorder symptoms and risk of LEA/RED-S (Sim and Burns, 2021 ). It consists of 28 items which were divided into four subscales (restraint, eating concern, shape concern, and weight concern) and a global score averaging the subscales, used as cut-off for eating disorder pathology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EDE-Q 6.0 was used to measure behavioral and cognitive symptoms of eating disorders the past 28 days (Fairburn and Beglin, 1994 ). The EDE-Q is based on the Eating Disorder Examination Interview which is considered as the gold standard in eating disorder assessment (Guest, 2000 ) and is one of the most used instruments to screen for eating disorder symptoms and risk of LEA/RED-S (Sim and Burns, 2021 ). It consists of 28 items which were divided into four subscales (restraint, eating concern, shape concern, and weight concern) and a global score averaging the subscales, used as cut-off for eating disorder pathology.…”
Section: Methodsmentioning
confidence: 99%
“…In female endurance athletes, the reported prevalence of LEA ranges between 8 and 56% when defined as energy availability <30 kcal/kg fat-free mass/day assessed with food and training records (Monyeki et al, 2014 ; Melin et al, 2015 ; Day et al, 2016 ; Muia et al, 2016 ; Heikura et al, 2017 ; Mccormack et al, 2019 ; Beermann et al, 2020 ). It has been suggested that assessing self-reported physiological symptoms of LEA using questionnaires, such as the Low Energy Availability in Females Questionnaire (LEAF-Q), provides a better assessment of the overall health status of an athlete than a snapshot of current energy availability using error-prone assessments of dietary energy intake and exercise energy expenditure (Heikura et al, 2017 ; Burke et al, 2018 ; Sim and Burns, 2021 ). When assessed as a LEAF-Q score ≥ 8, the LEA risk rate ranges from 31 to 80% in female endurance athletes (Melin et al, 2014 ; Folscher et al, 2015 ; Heikura et al, 2017 ; Carr et al, 2019 ; Ihalainen et al, 2021 ; Jesus et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the normal physical therapy review of systems, the first step in determining readiness to run after childbirth should include a thorough physical therapy evaluation (review of systems, 16 musculoskeletal examination, [17][18][19] and questions on pelvic health 20,21 ) as well as screening for impact readiness (musculoskeletal tolerance to impact), pelvic health symptoms, physiological variables (sleep, fatigue, nutrition, and systems review [22][23][24][25][26] ), and performing a running gait analysis (see Supplemental Digital Content Appendix A, available at: http://links.lww. com/JWHPT/A76, and Supplemental Digital Content Figure 1, available at: http://links.lww.com/JWHPT/ A77).…”
Section: Screening For Readiness To Run After Childbirthmentioning
confidence: 99%
“…Using this dance specific questionnaire as part of the onboarding process for dancers joining a dance company would be helpful and also as a yearly quantitative monitoring tool to support dancer health. Nevertheless, a recent review of questionnaires for low energy availability found that these were not so effective in assessing unintentional low energy availability with increased energy expenditure [8].…”
Section: Dance Specific Health Questionnairementioning
confidence: 99%